2014 International Conference on Communication and Signal Processing 2014
DOI: 10.1109/iccsp.2014.6950013
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of LDR and OPT 101 detectors in reflectance type PPG sensor

Abstract: Detection of blood volume change in the skin by using Photo plethysmogram (PPG) sensor is based on the principle that hemoglobin in the blood absorbs infrared light than the other tissue. Favorable optical window is around 990nm range. The reflectance type photoplethysmographic sensor is designed using two different detectors. Objective is to compare the response of PPG sensor by using Light Dependent resistors (LDR) and OPTlOI as a detector. Signal is recorded by placing the sensor on a finger tip for wavelen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…In addition, we plan parallel measurement of BP and HR parameters of the currently scanned person during execution of the whole MR scan sequence. For this purpose, we will apply photo-plethysmography (PPG) using optical sensors for non-invasive retrieval of vital information about the cardiovascular system from the skin surface [28,29]. Variations in the photo-detector signal are related to changes in the blood volume inside the tissue.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we plan parallel measurement of BP and HR parameters of the currently scanned person during execution of the whole MR scan sequence. For this purpose, we will apply photo-plethysmography (PPG) using optical sensors for non-invasive retrieval of vital information about the cardiovascular system from the skin surface [28,29]. Variations in the photo-detector signal are related to changes in the blood volume inside the tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional methods of estimating cardiac output generally artificially extract the feature of the waveform, such as the area under the curve of the waveform [19], and then, calculate the result through a formula. Deep learning is currently being applied in different medical fields, and it has been shown that the method of estimating cardiac output using deep learningoutperforms traditional models when the blood flow is unstable [20].…”
Section: Introductionmentioning
confidence: 99%
“…For this purpose, we apply the photoplethysmography (PPG) using an optical sensor for the non-invasive acquisition of vital information about the cardiovascular system from the skin surface [3]. This optical sensor complies with the requirements for working in the magnetic field environment with present radio frequency and electromagnetic disturbance [4]. Variations in the photo-detector signal are related to changes in the blood volume inside the tissue.…”
Section: Introductionmentioning
confidence: 99%